PROMOTING GOOD CORPORATE GOVERNANCE IN THE LANDS COMMISSION OF GHANA - Abdulai, A. (UDS International Journal of Development, 2023)
The search for an efficient land administration regime in Ghana has assumed prominence in recent times. Interventions including the National Land Policy 1999 and the Land Administration Project have sought to ensure that the management and regulation of land for various uses and transactions is done in a professional manner underpinned by a good governance architecture. However, the Lands Commission, which is the lead agency for the management of lands in the country is itself challenged in terms of good corporate governance. This paper reveals a defect in the Commission’s composition which is the fundamental basis of the governance challenges that have contributed to its inability to assert its authority and perform its functions appropriately. The Lands Commission suffers from poor balance of executive and non-executive directors in addition to political appointee domination. Keywords: Land Administration; Corporate Governance; and Fiduciaries